Effects of acupuncture and medical training therapy on depression, anxiety, and quality of life in patients with frequent tension-type headache: A randomized controlled study. (January 2023) - Schiller, Joerg; Niederer, Daniel; Kellner, Tim; Eckhardt, Isabelle; Egen, Christoph; Zheng, Wen; Korallus, Christoph; Achenbach, Johannes; Ranker, Alexander; Sturm, Christian; Vogt, Lutz; Gutenbrunner, Christoph; et al.
Objectives: To compare the effects of acupuncture and medical training therapy in combination or individually with usual care on quality of life, depression, and anxiety in patients with tension-type headache. Methods: In this single-center, prospective, randomized, controlled, unblinded trial, 96 adults (38.7(+/−13.3) years of age; 75 females/20 males/one dropout) with frequent episodic or chronic tension-type headache were randomized to one of four treatment groups (n = 24). The treatment groups received six weeks of either acupuncture or medical training therapy as monotherapies or in combination (12 interventions each), or usual care. We assessed depressiveness (PHQ-9), anxiety (GAD-7), and health-related quality of life (SF-12) as secondary outcome parameters at baseline, six weeks, three months, and six months after initiation of treatment. Linear mixed models were calculated. Results: Both, acupuncture (baseline to six-weeks change scores: mean: −2(standard deviation: 2.5 points), three months: −2.4(2.4), six-months −2.7(3.6)) and the combination of acupuncture and medical training therapy (−2.7(4.9), −2.2(4.0), −2.2(4.2)) (each within-group p < .05) significantly reduced depressiveness-scores (PHQ-9) to a greater extent than medical training therapy (−0.3(2.0), −0.5(1.6), −0.9(2.6)) or usual care alone (−0.8(2.9), 0.1(2.8), 0.2(3.6)). We found similar results with anxiety scores and the physical sum scores of the SF-12. No severe adverse events occurred. Conclusions: Acupuncture and the combination of acupuncture and medical training therapy elicit positive effects on depression, anxiety, quality of life, and symptom intensity in patients with episodic and chronic tension-type headache. Acupuncture appears to play a central role in mediating the therapeutic effects, underscoring the clinical relevance of this treatment. An additive benefit of the combination of both therapies does not appear to be relevant. Trial registration: Registered on 11 February 2019. German Clinical Trials Register, DRKS00016723.